2007
DOI: 10.1111/j.1728-4465.2007.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Ties of Dependence: AIDS and Transactional Sex in Rural Malawi

Abstract: In sub‐Saharan Africa, the exchange of sex for material support—labeled “transactional sex” by Western observers—is claimed by some to be a major driver of the AIDS pandemic. Transactional sex is described as akin to prostitution, a degraded form of sexual expression forced on vulnerable women by economic desperation. Using evidence from rural Malawi, we demonstrate that patron–client ties and a moral obligation to support the needy, which are fundamental to African social life, are central elements of transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
161
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(168 citation statements)
references
References 46 publications
7
161
0
Order By: Relevance
“…The Malawi National Statistical Office and ORC Macro (2005) estimated that in the age groups 15 -19 and 20 -24 years, 3.7% and 13.2% of females, and 0.4% and 3.9% of males were infected with HIV, respectively. Swidler and Watkins (2007) have suggested that economic imperatives may be driving the transactional nature of sexual exchange in these relationships. It is therefore important to design interventions that are gender sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…The Malawi National Statistical Office and ORC Macro (2005) estimated that in the age groups 15 -19 and 20 -24 years, 3.7% and 13.2% of females, and 0.4% and 3.9% of males were infected with HIV, respectively. Swidler and Watkins (2007) have suggested that economic imperatives may be driving the transactional nature of sexual exchange in these relationships. It is therefore important to design interventions that are gender sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Seeing transactional sex as guided by the same logic as patron-client relationships, Swidler and Watkins (2007) argue that redistribution of resources through sexual affairs is not just a matter of sexual satisfaction. It is also about keeping good connections and being respected by society.…”
Section: The Moral Grammar Of Transactional Sexmentioning
confidence: 99%
“…It is also about keeping good connections and being respected by society. Sponsoring younger women is applauded as morally good and rewarding, whereas an older rich man who keeps money to himself, hoarding his resources, or who 'eats alone', as the local Malawi saying goes, is gossiped about and vulnerable to witchcraft (Swidler;Watkins 2007). In Maputo, similar notions prevailed, sometimes in a vulgarized fashion, as in a popular song called "Patrão é Patrão" (Patron is Patron) by local music star MC Roger, where young women are asked to be more grateful for what they receive from rich men.…”
Section: The Moral Grammar Of Transactional Sexmentioning
confidence: 99%
See 2 more Smart Citations